REUSING TILING WASTE IN THE CONSTRUCTION OF PAVEMENTS - Belakhdar, Loubna .; Belachia, Mouloud .; Hebhoub, Houria . (Journal of Applied Engineering Science, 2019)
The factories of tiles manufacturing, ceramics, marble, tile and brick generate an important quantity of waste, their recovery meets economic and environmental objectives. The objective of our research is to study the possibility of the reuse of tile manufacturing waste as aggregates in the construction of pavements. To carry out this experimental study we have made characterization tests on all the materials used. The study investigates the influence of substitution of recycled tarred waste aggregates in mixtures of bituminous gravels with rates of 10, 20 and 30% on mechanical performance (Duriez stability) and compared the results obtained with composite control samples ordinary aggregates (0%). The results obtained show that the introduction of tiling waste into the formulation of a severe bituminous material has a positive influence on the mechanical performance.